ROLES AND INDICATION OF POWER RELATIONS BETWEEN INDONESIAN MUSLIM LEADER AND THE AMERICAN CHRISTIANS IN RICHARD LEWIS’ THE FLAME TREE - Ekawati, Rosyida (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
Novel is sometimes more powerful than other types of literature and art, as such novels are directed to the widest possible audience. They are dramatic works which show interesting qualities by drawing the readers’ interest. Novels also cultivate the imagination, contribute to and deepen the capacity for moral reflection. Novel about Indonesian Muslims, written by non-Indonesians, need to get more attention because the novel has the power to create the identity of Indonesian Muslims through its representation. The identity represented will be viewed not only by Indonesian Muslims but also by people all over the world. Critical Discourse Analysis (CDA) serves as the study’s main theoretical foundation and Fairclough’s Three-Dimensional Model of Discourse is used to analyze the roles of religious leaders and the indication of power relations between the Indonesian Muslim leader and the American Christians. Categorized data are analyzed predominantly using textual analysis, a qualitative method. Results reveal the roles of religious leader are significant in building the character of Indonesian Muslims. Further, power relations between the Indonesian Muslim leader and the American Christians are constructed by language and paralanguage used in their interaction and communication.Keywords: Critical Discourse Analysis (CDA), Indonesian Muslims, Kiai